A computational phenotype of disrupted moral inference in Borderline Personality Disorder - Siegel, JZ; Curwell-Parry, O; Pearce, S; Saunders, KEA; Crockett, MJ (Elsevier, 2020)
Background Borderline Personality Disorder (BPD) is a serious mental disorder characterized by marked interpersonal disturbances, including difficulties trusting others and volatile impressions of others’ moral character, often resulting in premature relationship termination. We tested a hypothesis that moral character inference is disrupted in BPD and sensitive to Democratic Therapeutic Community (DTC) treatment.